PERSEPSI AYAH TERHADAP PERAN DALAM PENGASUHAN ANAK USIA DINI - Muthia Sari; Maulida Nur; Novita Sari; Ratu Yustika Rini; Inten Risna (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Busy work makes fathers have to take advantage of the time to maximize the father's role in caring for early childhood. This study aims to look at fathers' perceptions of the father's role in early childhood care in families with working fathers and housewives. This research is qualitative research using the case study method. In-depth interviews are a technique for collecting data. There are three working fathers with wives who work as housewives involved in this study. The results show that fathers view parenting as something important. Fathers maximize time by filling in fun activities with children to build closeness and instill positive values. The motivation for father involvement in parenting, personal experience, and environmental influences are integrated into how fathers interpret parenting and the father's role in the care of early childhood as a whole. More positive the father's perception of the father's role in parenting, the higher the father's involvement in parenting.